Penerapan Penyajian Laporan Keuangan Berdasarkan SAK-ETAP Untuk Mengetahui Kinerja Keuangan UMKM Toko Angka Wijaya - Kartika, Aprilia; Nuraini, Airin (Jurnal Abdimas Dedikasi Kesatuan, 2020)
Small and Medium Micro Enterprises are businesses that have an important role in the economy in Indonesia because micro, small and medium enterprises aim to grow and develop their business in order to build a national economy. SMEs are also able to open new jobs for domestic workers,SMEs provide income for the country in the form of foreign exchange. To get a better UMKM, so that SMEs can compete with large business institutions in terms of economy and empowerment, SMES actors must be aware of the importance of applying financial statements. The purpose of this study was to find out how the application of financial statements based on SAK-ETAP on SMEs and how financial performance in SMEs was implemented. The author conducts research at the Wijaya Figures Store UMKM located on Jl. Endang Sumawijaya Kampung Sindang Barang, Bogor Regency. This research method uses a qualitative descriptive method. The results of the Angka Wijaya SMES research did not apply financial statement. This is because the SMES owner Angka Wijaya do not understand the financial statements based on SAK ETAP. During 2018 total assets, liability+equitycan be generated in the amount of IDR 386,558,000, profit of IDR 120,518,000 equity of IDR 366,229,000 and total net cash flow of IDR 261,238,000. The results of the wijaya store SMEs performance are calculated using profitability ratios based on profit from good sales and ussing on asset, meaning that the angka wijaya UMKMs are good in terms of sales and efficient in using assets, while SMES performance in capital usage is not good because of UMKM Angka wijaya is less efficient in capital Keywords: application of financial statement presentation based on sak-etap to know wijaya's financial performance in figures shop smes